1999
DOI: 10.1159/000010069
|View full text |Cite
|
Sign up to set email alerts
|

Total Fibronectin in Maternal Plasma as a Predictor for Preeclampsia

Abstract: Objective: To assess the ability of measuring total maternal plasma fibronectin in predicting the risk of developing preeclampsia. Method: In a cohort of 657 initially normotensive pregnant nulliparous women blood samples were collected at 26, 30 and 34 weeks of gestation. After delivery 3 groups were selected for measurement of total plasma fibronectin. The first group comprised 24 women who developed preeclampsia; the second 21 women who developed gestational hypertension, and the third 89 age-matched contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 23 publications
3
21
0
1
Order By: Relevance
“…Total fibronectin makes up the majority of fibronectin present in the circulation. In different studies, both total and cellular fibronectin levels were found to be elevated prior to onset of preeclampsia [9][10][11][12]. In the present study increased second trimester plasma levels of fibronectin in patients who later developed preeclampsia has been observed.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Total fibronectin makes up the majority of fibronectin present in the circulation. In different studies, both total and cellular fibronectin levels were found to be elevated prior to onset of preeclampsia [9][10][11][12]. In the present study increased second trimester plasma levels of fibronectin in patients who later developed preeclampsia has been observed.…”
Section: Discussionsupporting
confidence: 68%
“…The association of elevated plasma fibronectin in preeclampsia has been documented in previous studies indicating an endothelial cell dysfunction [12]. In the study of Gredmark et al, the positive predictive value in 26th gw was 57%, the specificity 97%, whereas the sensitivity was only 17% [11]. The authors concluded that total fibronectin might be useful to determine relative risks, but is a poor predictor in a low risk population.…”
Section: Discussionmentioning
confidence: 80%
“…Since the cFN isoform is localized primarily to the endothelium, it is considered to be a specific marker of endothelial injury [30]. Recently, Powers et al [14] showed that homocysteine-induced oxidative stress might result in endothelial dysfunction, as measured by plasma cFN levels.…”
Section: Parameters Of Oxidative Stress After Methionine Loadingmentioning
confidence: 99%
“…Early detection and timely assessments of the disease are essential to reduce the risks associated with the development of preeclampsia [1][2][3] . Uterine artery Doppler at 22-24 weeks was found to identify women at higher risk for the development of subsequent complications of placental insufficiency.…”
Section: Introductionmentioning
confidence: 99%